Pengembangan Perangkat Pembelajaran Berbasis Pendidikan Matematika Realistik untuk Meningkatkan Kemampuan Komunikasi Matematis - Lubis, Nurin Natiqoh; Lubis, Ikwan; ., Irvan (Journal Mathematics Education Sigma [JMES], 2025)
This research aims to develop PMR-based learning tools (Realistic Mathematical Approach) on sequences and series material to determine the level of validity, effectiveness and practicality of PMR-based learning tools, increase students' mathematical communication skills using the developed learning tools and process student answers. in solving questions on mathematical communication skills, and student responses to learning using PMR-based learning tools.This research is research using the research and development (RD) method using the ADDIE development research model: Analyze, Design, Development, Implementation, and Evaluation. The subjects of the research were 21 students in class VIII of SMP IT Khairul Imam for the 2022/2023 academic year. The types of data are qualitative data and quantitative data, data is analyzed qualitatively and quantitatively. The research instruments used were lesson plan assessment sheets from material and media expert lecturers, mathematics teachers, colleagues, tests of students' mathematical communication skills and student response questionnaires.The research results show that: (1) The PMR-based learning tools developed obtained interactive learning which was declared valid with an average of 4.31; (2) The PMR-based learning tools developed meet the criteria for learning practicality in terms of analysis of the results of observations of learning implementation. The value obtained in trial I was 3.03 (medium category). In trial II, the observation value for learning implementation increased to 3.88 (the "high" category); (3) The PMR-based learning tools developed meet the effectiveness criteria. (4) Based on the normalized gain index, it was found that in trial I there was an increase in students' mathematical communication skills with "low" criteria with a score of 0.30 (g ≤ 0.3) and in trial II there was an increase in scores with "medium" criteria. with a score of 0.42 (0.3 N-Gain ≤ 0.7).